Just for Fun: The Playful Image of Nanotechnology. - Milburn, Colin (NanoEthics, 2011)
In 1959, Richard Feynman suggested that the most compelling reason to pursue nanoscale research might be 'just for fun.' This article traces a history of playful images and ludic practices in nanotechnology. Two case studies-nanocars and nanosoccer-exemplify the ways in which scientific research mobilizes speculative futures, less through engineering design or stepwise protocol than through the recreational dynamics of play. Although such molecular toys might appear frivolous, they index the increasingly widespread conditions of play labor, or 'playbor', shaping today's technoculture. Exploring the processes of transmutation and transvaluation by which technological imaginaries are rendered operative, this article tells a story of how the nanoworld became an everyday reality by becoming a game.